12/15-lipoxygenase activity promotes efficient inflammation resolution in a murine model of Lyme arthritis - Jackson, Christa D.; Hilliard, Kinsey A.; Brown, Charles R. (Frontiers in Immunology, 2023)
Infection of C3H/HeJ (C3H) mice with Borrelia burgdorferi results in the development of a robust inflammatory arthritis that peaks around 3-4 weeks post-infection and then spontaneously resolves over the next few weeks. Mice lacking cyclooxygenase (COX)-2 or 5-lipoxygenase (5-LO) activity develop arthritis similar to wild-type mice but display delayed or prolonged joint resolution. Since 12/15-lipoxygenase (12/15-LO) activity is generally down-stream of both COX-2 and 5-LO activity and results in the production of pro-resolution lipids such as lipoxins and resolvins among others, we investigated the impact of 12/15-LO deficiency on the resolution of Lyme arthritis in mice on a C3H background. We found the expression of Alox15 (12/15-LO gene) peaked around 4-weeks post-infection in C3H mice suggesting a role for 12/15-LO in mediating arthritis resolution. A deficiency in 12/15-LO resulted in exacerbated ankle swelling and arthritis severity during the resolution phase without compromising anti-Borrelia antibody production and spirochete clearance. However, clearance of inflammatory cells was impeded. Therapeutic treatment of B. burgdorferi-infected C3H mice with lipoxin A4 (LXA4) near the peak of disease resulted in significantly decreased ankle swelling and a switch of joint macrophages to a resolving phenotype but did not directly impact arthritis severity. These results demonstrate that 12/15-LO lipid metabolites are important components of inflammatory arthritis resolution in murine Lyme arthritis and may be a therapeutic target for treatment of joint edema and pain for Lyme arthritis patients without compromising spirochete clearance.